Advocacy Coalition Framework in Environmental Governance Studies: Explaining Major Policy Change for A Large Dam Removal in Japan - Tomohiko Ohno (International Review of Public Policy)
This paper applied the Advocacy Coalition Framework (ACF) to environmental governance studies and examined the validity of policy change hypotheses in Japan, where few ACF studies exist despite the seemingly appropriate conditions to apply the ACF. While environmental governance has been studied for several decades, there is no prevailing research framework. I used the ACF to explain the policy process leading to Japan’s first large dam removal, a critical case of major policy change in environmental governance. Using data from interviews and newspaper articles, I identified advocacy coalitions, the events leading to the policy change, and the changes in coalition resources through discourse network analysis and other methods used in the ACF literature. Consequently, I found that the policy change hypotheses were valid and that coalition resources were significant intervening variables that lead to policy change. However, I also found the need for further refinements of the policy change hypotheses in the ACF. This paper confirms the utility of the ACF’s policy change hypotheses and research methods to understand the complex dynamics of environmental governance.